The Effects of Androgens on T Cells: Clues to Female Predominance in Autoimmune Liver Diseases? - Henze, Lara; Schwinge, Dorothee; Schramm, Christoph (Frontiers in Immunology, 2020)
The immune system responds differently in women and in men. Generally speaking, adult females show stronger innate and adaptive immune responses than males. This results in lower risk of developing most of the infectious diseases and a better ability to clear viral infection in women (1-5). On the other hand, women are at increased risk of developing autoimmune diseases (AID) such as rheumatoid arthritis, multiple sclerosis (MS), systemic lupus erythematosus (SLE), Sjögren’s syndrome, and the autoimmune liver diseases, autoimmune hepatitis (AIH) and primary biliary cholangitis (PBC) (6). Factors contributing to the female sex bias in autoimmune diseases include environmental exposure, e.g. microbiome, behaviour, and genetics including X chromosomal inactivation of genes. Several lines of evidence and clinical observations clearly indicate that sex hormones contribute significantly to disease pathogenesis and the role of estrogen in autoimmune diseases has been extensively studied. In many of these diseases, including the autoimmune liver diseases, T cells are thought to play an important pathogenetic role.We will use this mini-review to focus on the effects of androgens on T cells and how the two major androgens, testosterone and dihydrotestosterone, potentially contribute to the pathogenesis of autoimmune liver diseases (AILD).